(untitled) (Bangladesh Journal of Microbiology, 2020)
Food safety knowledge, attitudes, and street food suppliers and consumer behaviors of the capital city Dhaka were investigated. A cross-sectional study was conducted using questionnaires based on previous studies. Three main areas addressed in the surveys and statistical analysis are; 1) statistical data including gender, age, education, income, food safety training, and specific elements related to the work experience of suppliers, 2) knowledge of food safety such as the awareness of consumers and suppliers concerning pathogenic microbes that cause food poisoning, food and personal hygiene, proper cleaning procedures and high-risk groups, and 3) list of food handling attitude and behavior of subjects. Results showed food safety knowledge of street vendors in the High-tech Industries Development Zone was the lowest, where education levels are generally relatively low. Food safety attitudes of the youngest consumers were significantly better than those of older age groups. Street vendors were relatively poor in carrying out safe food handling, with only 27.6% using or being fully equipped with hand-washing facilities, although more than 50% of vendors were not wearing clean and tidy clothes and masks. Steps should be taken to improve street food stall operating conditions and facilities, including access of potable water, providing clean protected structures, and efficient waste collection and disposal systems that can promote the plans and strategies to improve street food safety of Dhaka city and Bangladesh as a whole. Bangladesh J Microbiol, Volume 37 Number 2 December 2020, pp 48-51